2018
DOI: 10.1002/fsn3.777
|View full text |Cite
|
Sign up to set email alerts
|

Production of nutrient‐enhanced millet‐based composite flour using skimmed milk powder and vegetables

Abstract: The aim of this study was to develop a nutrient‐enhanced millet‐based composite flour incorporating skimmed milk powder and vegetables for children aged 6–59 months. Two processing methods were tested to optimize nutrient content and quality of millet‐based composite flour, namely germination for 0, 24 and 48 hr and roasting at 80, 100, and 140°C. The amount of ingredients in the formulation was determined using Nutri‐survey software. Germinating millet grains for 48 hr at room temperature significantly (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 55 publications
3
43
4
2
Order By: Relevance
“…In addition, it is observed that the treatment improves the energy intake in cassava flours but decreases in corn flours. The percentage coverage regardless of age of these different flours is similar to that of Tumwine, Atukwase, Tumuhimbise, Tucungwiirwe, and Linnemann (), on millet composite flours. Proteins play an important role in tissue formation, development and growth of children.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, it is observed that the treatment improves the energy intake in cassava flours but decreases in corn flours. The percentage coverage regardless of age of these different flours is similar to that of Tumwine, Atukwase, Tumuhimbise, Tucungwiirwe, and Linnemann (), on millet composite flours. Proteins play an important role in tissue formation, development and growth of children.…”
Section: Resultssupporting
confidence: 71%
“…This implies that for a good contribution, mineral sources such as Moringa should be provided. These results are much lower than those of Tumwine et al (), whose calcium coverage was as high as 95.50%. Concerning iron, it should be noted that the percentage of contribution is influenced by the treatment.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…In this study, it was observed that the addition of skimmed milk powder and vegetable flours was associated with higher PV, FFA and TBA values over the storage period. The results from an earlier study by Tumwine et al 27 indicated that the millet-based composite flour had a higher fat content (3.7%) compared to the control (1.6%). The high fat content of the composite flour was due to the addition of pumpkin seed flour since the powdered milk used was skimmed and had a lower fat content not exceeding 0.5%.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, it was observed that the addition of skimmed milk powder and vegetable flours was associated with higher PV, FFA and TBA values over the storage period. The results from an earlier study by Tumwine et al . indicated that the millet‐based composite flour had a higher fat content (3.7%) compared to the control (1.6%).…”
Section: Discussionmentioning
confidence: 93%